The Case of “Missing Parent(s)”: Children’s Literature in Indian Writing in English - Verma, Raj Gaurav (SARE: Southeast Asian Review of English, 2018)
This paper explores the transition from the theme of the “lost child” to that of “lost parent(s)” in children’s literature in India. In the case of the “lost child,” the child is lost but the parents/family are together, and for the lost child it is s/he who is alone and has lost his or her parents. Therefore, in traditional narratives, if a child is lost, a child is lost to his or her parents, and so are the parents lost to the child. But in a strange reversal of this pattern in contemporary Indian children’s literature, it is now common that the child is present but the parent or parents are missing. In this leap, the writers of children’s literature have deviated from the established structure of “home-away-home” in which the child is lost to a condition when either or both parents are missing. Children’s literature is traditionally embedded within the paradoxical nature of the adult/child binary and it is common for writers of children’s literature to discard the adult and centralize the child. However, despite the peripheral treatment of parents in children’s literature, this paper argues that the absolute necessity of parental care still remains for the child “inside” and “outside” the text. The need for parents still remains the same in contemporary times, yet children’s texts also show how a child is affected when either or both parents are absent. Contemporary Indian children’s literature addresses this issue of “missing parents” by introducing “alternate parenting” into the narrative.